2022
DOI: 10.1038/s41388-022-02569-3
|View full text |Cite
|
Sign up to set email alerts
|

Altered gut microbiome composition by appendectomy contributes to colorectal cancer

Abstract: Appendectomy impacts the homeostasis of gut microbiome in patients. We aimed to study the role of appendectomy in colorectal cancer (CRC) risk through causing gut microbial dysbiosis. Population-based longitudinal study (cohort 1, n = 129,155) showed a 73.0% increase in CRC risk among appendectomy cases throughout 20 years follow-up (Adjusted sub-distribution hazard ratio (SHR) 1.73, 95% CI 1.49–2.01, P < 0.001). Shotgun metagenomic sequencing was performed on fecal samples from cohort 2 (n = 314). Gut micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 42 publications
(66 reference statements)
1
32
1
Order By: Relevance
“…The research suggests that postcholecystectomy changes in bile acid metabolism and disruptions in gut microbiota may be contributing factors to the development of colorectal cancer 54 . Furthermore, results from a study conducted in China suggest that the gut microbiota may play a crucial role in the development of colorectal cancer induced by appendectomy 55 . However, our data did not fully support this conclusion, possibly because some of our positive patients had a history of appendicitis or cholecystitis rather than surgical removal of these organs.…”
Section: Dissusioncontrasting
confidence: 58%
“…The research suggests that postcholecystectomy changes in bile acid metabolism and disruptions in gut microbiota may be contributing factors to the development of colorectal cancer 54 . Furthermore, results from a study conducted in China suggest that the gut microbiota may play a crucial role in the development of colorectal cancer induced by appendectomy 55 . However, our data did not fully support this conclusion, possibly because some of our positive patients had a history of appendicitis or cholecystitis rather than surgical removal of these organs.…”
Section: Dissusioncontrasting
confidence: 58%
“…A predominance of bacterial species previously reported to be associated with CRC was noted in our cohort, including F. nucleatum, 9,[19][20][21][22][23] Parvimonas micra, 21,24,25 Clostridium symbiosum. 24,26 We also identified species that have been reported to be associated with CRC but previously found in gut microbiome Collinsella aerofaciens, 27,28 and in plasma circulating microbiome, Gemella morbillorum 25 (Fig. 1D, Supplementary Table 1, Supplemental Digital Content 1, http://links.lww.com/SLA/E740).…”
Section: Bacterial Communities In Tumor Versus Normal Tissuementioning
confidence: 72%
“…35 In addition, C. aerofaciens, associated with the previous appendectomy demonstrated the highest proportion of differential abundance within YORC compared with matched normal tissues. 27 Distinct from these findings of YORC, the LORC cohort contains what might be considered more "typical" bacteria entities including species such as F. nucleatum and P. micra. This potentially suggests that previous CRC-related work had included mostly LORC patients, and likely underlines again the need to design studies enriching for YORC to allow in-depth study of it as a distinct entity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased risk of CRC in post-appendectomy populations were statistically significant in five out of nine studies comprising of case-control and cohort studies that yielded data on observed CRC cases between control and post-appendectomy populations, with hazard ratios (HR) for CRC ranging from 1.14 to 2.99 in the post-appendectomy cohorts as compared to control. [6][7][8][9][10] In two studies, this increased risk was found to be even more apparent in subgroups consisting of patients with an older age, defined by Shi et al 8 as an age of 50 and older and by Wu et al 7 as an age of 60 and older at the time of appendectomy and corresponding to an HR of 2.02; 1.71-2.40 and 1.24; and 1.06-1.45, respectively. Two studies (Wu et al, 7 Lee et al 9 ) identified that the risk of CRC was highest in the first 3 years post-appendectomy, and it seems that after which the risk for CRC returns to baseline.…”
Section: Epidemiological Observation Of the Relationship Between Prev...mentioning
confidence: 96%